Estudo fitoquímico de extratos polares e infusão das folhas de Terminalia catappa L. (Combretaceae) e avaliação de suas atividades antiulcerogênica e mutagênica - Mininel, Francisco José [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Terminalia catappa Linn. belongs to Combretaceae family and is commonly called almond-the-beach or sun hat.The Combretaceae family gathers numerous species that has been studied for its use by the population for medicinal purposes. It is from Malaysia, but often cultivated and very characteristic of the Brazilian coast. From the alcoholic extract of the leaves were detected as main constituents the major substance punicalagin (α and β anomers), the punicalin compound, gallagic acid and ellagic acid. It was identified as well, the 1,2,3-Tri-O-galloyl-β-D-glucose substances, and possible isomers, 1,6-Di-O-galloyl-β-D-glucose, HHDP acetilglicoside, HHDPhesoside, ellagic acid hexoside, gallagic acid and apigenin 8-C (2 '-galloyl)-β-Dglucopyranosyl. These metabolites were confirmed by FIA-ESI-IT-MSn experiments (Direct Flow Analysis Electrospray ionization-Ion-Trap Tandem Mass Spectrometry) and High Performance Liquid Chromatography (HPLC) coupled with diode array (PDA). Ellagic acid, gallic acid and methyl gallate were confirmed by standard coinjection experiments. Punicalagin was detected and isolated from the hydromethanol fraction as a mixture of anomers experiments and confirmed by 1H and 13C NMR, mono- and bi-dimensional. The ethyl acetate fraction from fractionation of the hydroalcoholic extract by MPLC (Medium Pressure Liquid Chromatography) allowed the isolation of galágico acid metabolites and 8 apigenin-C (2'- galloyl) -β-Dglucopyranosyl. The absolute configuration of anomers of the compound of punicalagin and apigenin 8-C (2'-galloyl) -β-D- glucopyranosyl was established by experiments circular dichroism (CD). Quantitative determination of the main secondary metabolites was performed by HPLC-PDA, thus allowing the determination of concentration and content (%) of metabolites present in the alcoholic extract. They were first quantified in hydroalcoholic extract of this species, the...

Terminalia catappa Linn. pertence à Família Combretaceae e é comumente chamada amendoeira-da-praia ou chapéu de sol. A família Combretaceae reúne numerosas espécies que têm sido estudadas por seu uso pela população para fins medicinais. É originária da Malásia, mas, muitas vezes, cultivada e muito característica da costa brasileira. A partir do extrato hidroalcoólico das folhas, foram detectados como constituintes principais a substância majoritária punicalagina (anômeros α e β), o composto punicalina, ácido galágico e ácido elágico. Identificouse, também, as substâncias 1,2,3-Tri-O-galoil-β-D-glicose e possíveis isômeros, 1,6- Di-O-galoil-β-D-glicose, HHDP-acetilglicosídeo, HHDP-hexosídeo, ácido elágico hexosídeo, ácido galágico e apigenina 8-C-(2'-galoil)-β-D-glicopiranosil. Estes metabolitos foram confirmados por experimentos FIA-ESI-IT-MSn (Direct Flow Analysis-Electrospray ionization-Íon Trap-Tandem Mass Spectrometry) and High Performance Liquid Chromatography (HPLC) acoplada a arranjo de fotodiodos (PDA). Ácido elágico, ácido gálico e galato de metila foram confirmados por experimentos de co-injecção de padrão. Punicalagina foi detectada e isolada da fração hidrometanólica como uma mistura de anômeros e confirmada por experimentos de RMN 1H e 13C, mono e bidimensionais. O fracionamento da fração acetato proveniente do extrato hidroalcoólico por MPLC (Medium Pressure Liquid Chromatography) permitiu o isolamento dos metabólitos ácido galágico e apigenina 8-C-(2'-galoil)-β-D-glicopiranosil. A configuração absoluta dos anômeros da punicalagina e do composto apigenina 8-C-(2'-galoil)-β-D-glicopiranosideo foi estabelecida por experimentos de dicroísmo circular (DC). A determinação quantitativa dos principais metabolitos secundários foi realizada por HPLC-PDA, possibilitando, assim, a determinação da concentração e teor (%) de...
Keywords: Taninos; Espectrometria de massa; Extratos vegetais; Dicroismo circular; Terminalia; Mass spectrometry